+0  
 
0
72
1
avatar

Solve (x - 3)(x + 1)(x - 4)(x + 2) = -6.

 May 13, 2020
 #1
avatar+111456 
+1

(x - 3) (x + 1) ( x - 4) (x + 2)  =  - 6

 

(x^2 - 2x - 3) (x^2 - 2x - 8)  =  - 6

 

Let  x^2  - 2x  =  a

 

So we have

 

(a - 3) (a - 8)  =  - 6

 

a^2  - 11a  + 24  = -6

 

a^2  - 11a  + 30  =  0            factor

 

(a - 5) ( a - 6)  =  0

 

Setting each factor to 0  and solving for x produces

 

a = 5      or      a  =6

 

So

 

x^2 - 2x  = 5                                or                                           x^2  - 2x  = 6

                                 complete the square on x

 

x^2 - 2x + 1  = 5 + 1                                                                 x^2 - 2x  + 1  =  6 + 1

 

(x - 1)^2  = 6                                                                            (x - 1)^2  =   7

                                 take  both   roots

 

x - 1  =  ±√6                                                                              x - 1  =  ±√7

 

x = ±√6 + 1                              or                                              x  =  ±√7  + 1

 

 

 

cool cool cool                                         

 May 13, 2020

51 Online Users

avatar